In vitro anti-TB properties, in silico target validation, molecular docking and dynamics studies of substituted 1, 2, 4-oxadiazole analogues against Mycobacterium tuberculosis. (1st January 2021) - Deb, Pran Kishore; Al-Shar'i, Nizar A.; Venugopala, Katharigatta N.; Pillay, Melendhran; Borah, Pobitra
Abstract: The alarming increase in multi- and extensively drug-resistant (MDR and XDR) strains of Mycobacterium tuberculosis (MTB) has triggered the scientific community to search for novel, effective, and safer therapeutics. To this end, a series of 3, 5-disubstituted-1, 2, 4-oxadiazole derivatives (3a–3i ) were tested against H37Rv, MDR and XDR strains of MTB. Of which, compound 3a with para-trifluorophenyl substituted oxadiazole showed excellent activity against the susceptible H37Rv and MDR-MTB strain with a MIC values of 8 and 16 µg/ml, respectively. To understand the mechanism of action of these compounds (3a–3i ) and identify their putative drug target, molecular docking and dynamics studies were employed against a panel of 20 mycobacterial enzymes reported to be essential for mycobacterial growth and survival. These computational studies revealed polyketide synthase (Pks13) enzyme as the putative target. Moreover, in silico ADMET predictions showed satisfactory properties for these compounds, collectively, making them, particularly compound 3a, promising leads worthy of further optimisation.